Kant’s dialectics: the doctrine of development or logic of visibility - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The presence of two versions of dialectics in the philosophical work of I. Kant is noted: the first one, proposed by him in the pre-critical period, is connected with the traditional doctrine of development, opposing mechanicism and speculative metaphysics; the second one, developed in the critical period, is the logic of appearances, what the mind has to overcome on the way to truth. It is shown that in the pre-critical period the philosopher initiated the process of spontaneous dialectisation of natural sciences and posed a number of questions far beyond Newtonian mechanicism.